PENGARUH TRANSFER PRICING, THIN CAPITALIZATION, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2021 – 2023 - Permatasari, Putri Indah; Handayani, Alberta Esti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The purpose of this study is to analyze the effect of transfer pricing, thin capitalization, and profitability on tax avoidance in food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2021-2023 period.Methods: This study employed a quantitative method, utilizing secondary data in the form of company financial reports obtained through the IDX website and documentary techniques. The population used was the food and beverage subsector on the IDX for the 2021-2023 period, with a sample of 22 companies selected purposively. The analysis method used was descriptive analysis.Results: The study's F-test revealed that transfer pricing, thin capitalization, and profitability variables collectively had a significant impact on tax avoidance. Meanwhile, the t-test results showed that transfer pricing and thin capitalization variables were associated with tax avoidance. Meanwhile, the profitability variable did not affect tax avoidance. Keywords: Transfer Pricing, Thin capitalization, Profitability, Tax avoidance